Maintaining the status hierarchy: the effect of threat on perceptions of reappropriated racial slurs - O'Dea, Conor James (Kansas State University, 2019)
Racial slurs are terms that disparage individuals on the basis of their racial group. Interestingly, racial slurs are often reappropriated and used among the targeted group as a means of affiliation rather than derogation (subversive use; Bianchi, 2014). The current studies examined majority group members’ resistance to affiliative slur use. Previous research has shown (correlationally) that majority group members higher in socially dominant attitudes perceived a Black individual using “nigga” affiliatively toward a White person as threatening, and this threat was related to more negative perceptions of the reappropriated slur use and greater perceptions that prejudice toward Black individuals is justified (O’Dea & Saucier, revision in preparation). Extending this work, the current studies causally examined these effects by testing whether a high threat prime from Black individuals was associated with more negative attitudes toward a Black individual using a reappropriated term (i.e., “nigga”) affiliatively toward a White individual (Study 1) and toward another Black individual (Study 2), compared to a low threat condition or to a control condition. Further, the current studies examined whether participants’ existing socially dominant beliefs interacted with threat condition (high threat, low threat, control) in predicting their perceptions of reappropriated racial slur use. Consistent with my hierarchy defense hypothesis, the current findings showed that greater socially dominant attitudes were associated with more negative perceptions of “nigga” used affiliatively by a Black individual toward a White individual (Study 1) but not by a Black individual toward a Black individual (Study 2) which supported my competing hypothesis that intragroup uses of reappropriated racial slurs are not perceived as threatening. These relationships were largely unaffected by threat condition in either study. Further, while people higher in socially dominant attitudes were shown to be more resistant to intragroup uses of racial slurs, people across the spectrum of social dominance did not perceive slur reappropriation very negatively in either intergroup (Study 1) or intragroup (Study 2) uses. These findings extend previous research on the subversive perspective (Bianchi, 2014). Indeed, slur reappropriation may have a prosocial benefit of helping marginalized groups cope with prejudice (Galinsky et al., 2013) and may even be used to affiliate between groups. However, when used to bridge group boundaries, it may moderately increase highly socially dominant White peoples’ negative perceptions of slur reappropriation and their subsequent perceptions that prejudice toward Black individuals is acceptable.
Keywords: Racial slurs; Prejudice; Social Dominance; Prejudice reduction; Coping with prejudice; Combating prejudice